2021
DOI: 10.1021/acs.langmuir.0c03094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Superhydrophobic Surface Structure on Droplet Jumping Velocity

Abstract: The coalescence-induced droplet jumping on superhydrophobic surfaces is fundamentally significant from an academic or practical viewpoint. However, approaches to enhance droplet jumping velocity are very limited. In this work, the effect of structural parameters of the triangular prism on droplet jumping is studied systematically. The results indicate that droplet jumping velocity can be greatly increased by exploiting structure effects, which is a promising reinforcement method. When the height and apex angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Сложившаяся ситуация сводится к простой баллистической задаче для тела, движущегося в поле земного тяготения при наличии вертикального потока среды. В настоящее время подобные прыжки капель интересуют широкий круг исследователей, изучающих физические системы различного типа [31][32][33][34].…”
Section: описание экспериментальной процедурыunclassified
“…Сложившаяся ситуация сводится к простой баллистической задаче для тела, движущегося в поле земного тяготения при наличии вертикального потока среды. В настоящее время подобные прыжки капель интересуют широкий круг исследователей, изучающих физические системы различного типа [31][32][33][34].…”
Section: описание экспериментальной процедурыunclassified
“…The research on nanoscale droplet confluence by molecular dynamics simulations also shows that the jumping velocity can be significantly increased by constructing individual grooves, ridges, or more hydrophobic strips on the superhydrophobic surface with dimensions comparable to the radius of the coalescing droplets. , The above study analyzed the mechanism of enhancing droplet jumping velocity by geometric structures and confirmed that macroscopic structures can effectively enhance the efficiency of coalescence-induced droplet jumping, but this is still a long way from achieving large-scale efficient droplet jumping. On the one hand, previous studies have focused on the jumping of individual droplets, usually studying only the effect of individual macroscopic structures on droplet jumping, which cannot be directly applied to large scales. On the other hand, the enhancement of droplet jumping by macrostructures is dependent on the relative size of coalescing droplets and the relative positions of droplets and macrostructures. , Most of the droplets in efficient droplet jumping reported in previous studies are artificially placed or randomly generated.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Vahabi et al 22 integrated a macro-ridge on superomniphobic surfaces and achieved a high energy conversion efficiency of 18.8%. Recently, the energy conversion efficiency has been further increased to around 50% using surface structures, including fibers, 23 triangular prism, 24 and egg tray-like structure. 25 of liquid bridge impact and the in-plane momentum, which can thus be converted into the perpendicular component more effectively.…”
Section: ■ Introductionmentioning
confidence: 99%